Empowering Iraqi Female Students Toward Healthier Preconception Behaviors: Memberdayakan Siswa Perempuan Irak Menuju Perilaku Prakonsepsi yang Lebih Sehat - Arief, Nawres Jameel; Naji, Arkan Bahlol (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the efficacy of a health beliefs model-based intervention in enhancing pre-pregnancy health behaviors among female college students at the University of Baghdad's English Department. Despite initial similarities in health behaviors between the control (n=72) and experimental (n=72) groups, significant improvements were observed in the experimental group post-intervention, indicating a successful impact of the intervention on health behaviors (first posttest: p < 0.001; second posttest: p < 0.001). Conducted from October 2023 to March 2024, this randomized controlled trial utilized pretests, posttests, and intervention sessions to evaluate outcomes. Results underscore the potential of incorporating such targeted health programs into existing university health curricula to foster better pre-pregnancy health practices among young women, thereby improving long-term health outcomes. This intervention fills a crucial gap by demonstrating sustainable behavior change, which is essential for proactive health management in this demographic. Keywords: Expanded Health Belief Model, Preconception, Health Behaviors, Female Collegians